Hemoglobin D-Punjab heterozygous encountered in Assam: a case report - Debnath, Tanushree; Pathak, Mauchumi S.; Borah, Monalisha S.; Phimu, Zhoyio L.; Gogoi, Ananya (International Journal of Research in Medical Sciences, 2024)
Hemoglobin (Hb) D-Punjab is a haemoglobin variant with a point mutation in beta globin gene. A case of Hb D was encountered during screening of Hb variants among undergraduate students. With a prevalence rate of 2% in India, Hb D is generally rare in the Northeast region of India. Among the 200 screened cases, one Hb D heterozygous was detected by analysing the blood sample of the subject with an automated haematology analyser for complete blood count (CBC) and by using high performance liquid chromatography (HPLC) based Hb typing method. The haematological parameters were done in cell counter with Hg % 15.1 g/dl, mean corpuscular volume (MCV) 95 fl and mean corpuscular hemoglobin (MCH) 32.2 pg. The platelet value was high and high mean corpuscular hemoglobin concentration (MCHC) was obtained and the HPLC based haemoglobin typing was done with A2-2.9, A0-53.3, F- <0.8 area percentage and unknown window with 38.2 area percentage (retention time 3.86). Hb D Punjab heterozygous case has been reported in this report as prevalence of Hb D Punjab is very rare in the state of Assam.